2014
DOI: 10.1371/journal.pone.0099215
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Seedborne Bacterial Pathogens with Host and Non-Host Plants in Relation to Seed Infestation and Seedling Transmission

Abstract: The ability of seed-borne bacterial pathogens (Acidovorax citrulli, Clavibacter michiganensis subsp. michiganensis, Pseudomonas syringae pv. tomato, Xanthomonas euvesicatoria, and Pseudomonas syringae pv. glycinea) to infest seeds of host and non-host plants (watermelon, tomato, pepper, and soybean) and subsequent pathogen transmission to seedlings was investigated. A non-pathogenic, pigmented strain of Serratia marcescens was also included to assess a null-interacting situation with the same plant species. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…The finding in the current study that Xanthomonas axonopodis pv. vignicola was able to colonize the seeds of some nonhost crops, and to be transmitted systemically from floral systems of millet and sorghum to the developing seedling is in agreement with previous reports by Darasse et al, 1 Dutta et al 4 and Darsonval et al, 26 Similar observations were also reported by Dutta et al 4 However, this study also demonstrated that sorghum and millet plants arising from contaminated seeds were unable to serve as reservoirs of the pathogen, and to subsequently cross-contaminate cowpea plants with the pathogen when the crops were grown together.…”
Section: Discussionsupporting
confidence: 93%
“…The finding in the current study that Xanthomonas axonopodis pv. vignicola was able to colonize the seeds of some nonhost crops, and to be transmitted systemically from floral systems of millet and sorghum to the developing seedling is in agreement with previous reports by Darasse et al, 1 Dutta et al 4 and Darsonval et al, 26 Similar observations were also reported by Dutta et al 4 However, this study also demonstrated that sorghum and millet plants arising from contaminated seeds were unable to serve as reservoirs of the pathogen, and to subsequently cross-contaminate cowpea plants with the pathogen when the crops were grown together.…”
Section: Discussionsupporting
confidence: 93%
“…Seedborne bacterial pathogens act as primary inoculum source for many important vegetable diseases and despite prophylactic measures adopted, epidemics due to seedborne inoculum continue to occur (Dutta et al ., ). The clustered or aggregated dispersal pattern of diseased tomato fields in Iranian provinces, best described by beta binomial probability distribution (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Owing to the importance of seed transmission in emergence of diseases in new planting areas, the processes involved in the transmission of microorganisms from plant to seed have been mainly documented for phytopathogenic agents. The molecular determinants involved in successful transmission of microorganisms from plant to seed have been notably studied in bacteria related to the Xanthomonas genus ( Darsonval et al, 2008 ; Darsonval et al, 2009 ; Darrasse et al, 2010 ; Dutta et al, 2014 ) and fungi that belonged to Alternaria brassicicola ( Pochon et al, 2012 ; Pochon et al, 2013 ). Key molecular determinants like the bacterial Type III Secretion System ( Darsonval et al, 2008 ), bacterial adhesins ( Darsonval et al, 2009 ), fungal class III histidine-kinase or dehydrin like proteins ( Pochon et al, 2013 ) have been shown to be involved in seed transmission.…”
Section: Introductionmentioning
confidence: 99%